2022
DOI: 10.3390/v14061267
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequencing of Tick-Borne Encephalitis Virus Directly from Clinical Samples: Comparison of Shotgun Metagenomic and Targeted Amplicon-Based Sequencing

Abstract: The clinical presentation of tick-borne encephalitis virus (TBEV) infection varies from asymptomatic to severe meningoencephalitis or meningoencephalomyelitis. The TBEV subtype has been suggested as one of the most important risk factors for disease severity, but TBEV genetic characterization is difficult. Infection is usually diagnosed in the post-viremic phase, and so relevant clinical samples of TBEV are extremely rare and, when present, are associated with low viral loads. To date, only two complete TBEV g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…A phylogenetic tree was constructed from the consensus genome sequences of the MTBFs sequenced in this study, a TBEV-Sib sequence from Genbank [note the authors do not have a TBEV-Sib isolate available for these studies], and a West Nile virus strain NY99 previously sequenced in the author’s laboratory, as an outgroup ( Figure 1 ). Overall, the MTBFs showed the expected relationship at the consensus genome level as reported in previous studies [ 9 , 11 , 27 , 28 , 29 ] with AHFV and KFDV closely related to each other (considered as genotypes), TBEV-FE, TBEV-Eur and OHFV closely related to each other, and POWV and DTV closely related to each other (considered as genotypes).…”
Section: Resultssupporting
confidence: 81%
“…A phylogenetic tree was constructed from the consensus genome sequences of the MTBFs sequenced in this study, a TBEV-Sib sequence from Genbank [note the authors do not have a TBEV-Sib isolate available for these studies], and a West Nile virus strain NY99 previously sequenced in the author’s laboratory, as an outgroup ( Figure 1 ). Overall, the MTBFs showed the expected relationship at the consensus genome level as reported in previous studies [ 9 , 11 , 27 , 28 , 29 ] with AHFV and KFDV closely related to each other (considered as genotypes), TBEV-FE, TBEV-Eur and OHFV closely related to each other, and POWV and DTV closely related to each other (considered as genotypes).…”
Section: Resultssupporting
confidence: 81%
“…To overcome these difficulties, the targeted enrichment of viral genomes from clinical samples using PCR has been used to reduce the nonspecific reads, streamline the bioinformatics analysis, and allow greater accuracy compared with metagenomics [ 31 ]. Recent studies have demonstrated that amplicon-based approaches offer greater genome coverage and higher sensitivity than mNGS [ 40 , 41 , 42 , 43 ]. These protocols are designed to amplify short and overlapping amplicons (about 1000 bp or less) across the genome and have been used to sequence the Zika virus, Crimean–Congo hemorrhagic fever virus, and SARS-CoV-2 from clinical samples [ 40 , 41 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the advantages of NGS panels, they have also been evaluated and tested for the multiple detection and determination of various foodborne pathogens. Prior to the use of NGS panels, the detection and identification of foodborne pathogens was conducted using 16S rRNA sequencing based on Sanger sequencing, 16S rRNA-based metagenome and random genome sequencing-based shotgun metagenomics approaches ( Bridier, 2019 ); however, these detection methods produce an overabundance of sequence information ( Zakotnik et al, 2022 ). To overcome this problem, NGS panels were developed and evaluated using specific primer sets, generally targeting the virulence factors and antibiotic resistance genes of foodborne pathogens.…”
Section: Introductionmentioning
confidence: 99%